8. Aedes Mosquitoes Abundance In Relation To Some Climatic Factors In Banda Aceh City, Indonesia - Farida Athaillah; Muhammad Hambal; Yudha Fahrimal; Muttaqien Bakri; Ellyawardani Ellyawardani; Henni Vanda; Abu Hassan Ahmad (The Faculty of Veterinary Medicine of Syiah Kuala University, 2016)
Dengue viruses and their mosquito vectors as an endemic disease in Indonesia are sensitive to their environment. The rising incidence of dengue is influenced by many factors, climate is one of them. Temperature, rainfall and humidity have well-defined roles in the transmission cycle. Changes in these conditions may contribute to increasing incidence. The purpose of this research was to determine the correlation between the dengue vector abundance and some climatic factors (temperature, rainfall and humidity) in Banda Aceh city after the tsunami. We also examined the potential effects of climate variations on dengue epidemiological pattern in indoor and outdoor of tsunami affected areas in Banda Aceh City during January – December 2010. Data processing was performed using SPSS and will be presented in tabular form. Pearson correlation test for parametric test and Spearman correlation coefficients for non-parametric test were performed to investigate the overall correlation between Aedes eggs abundance rates and some meteorological variables such as temperatures (0C), relative humidity (RH), and rainfall (RR). The result showed that the total egg populations in indoor and outdoor of tsunami affected areas are not significantly different among those factors. There was a positive correlation between eggs abundance and rainfall, but negatively correlated with temperature and relative humidity. From this result we can conclude that the abundance of Aedes eggs is not significantly correlated to temperature and humidity in indoor and outdoor of tsunami affected areas in Banda Aceh City.